2019
DOI: 10.1136/bmjopen-2019-032779
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable risk factors related to burnout levels in the medical workplace in Taiwan: cross-sectional study

Abstract: ObjectivesTo detect the combined effects of lifestyle factors on work-related burnout (WB) and to analyse the impact of the number of weekend catch-up sleep hours on burnout risk in a medical workplace.DesignCross-sectional study.SettingHospital-based survey in Taiwan.ParticipantsIn total, 2746 participants completed the hospital’s Overload Health Control System questionnaire for the period from the first day of January 2016 to the end of December 2016, with a response rate of 70.5%. The voluntary participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 39 publications
4
13
1
3
Order By: Relevance
“…Siu et al ’s study did not find that exercise was a stress-relieving factor against burnout. 20 However, the positive effects of exercise on burnout have been seen in some studies in Taiwan, 46 France 9 and the USA, 48 similar to the findings of this study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Siu et al ’s study did not find that exercise was a stress-relieving factor against burnout. 20 However, the positive effects of exercise on burnout have been seen in some studies in Taiwan, 46 France 9 and the USA, 48 similar to the findings of this study.…”
Section: Discussionsupporting
confidence: 85%
“…20 Although 24.8% of the respondents in our sample fell into the ‘at-risk’ category for alcohol use, this level of drinking was not correlated with burnout which was also similar to Siu et al ’s HK study and a Taiwan study on doctors. 46 In contrast, studies on US physicians have shown that alcohol abuse and dependence can be related to burnout. 26 These findings may suggest that HK physicians are less likely to turn to alcohol as a coping mechanism for stress.…”
Section: Discussionmentioning
confidence: 98%
“…Múltiples publicaciones han descrito la asociación entre las horas de sueño y el burnout, indicando una relación inversa entre ambos, además de múltiples efectos adversos, tanto en la salud física como mental. 30,31 En lo que respecta al contexto laboral, se observó una asociación significativa entre el cansancio al final de la jornada y el auto-reporte de burnout. Particularmente, realizar turnos de urgencia y un mayor número de horas en la jornada laboral, no se asociaron significativamente con una mayor tendencia al burnout.…”
Section: Discussionunclassified
“…Pese a ese potencial sesgo, los resultados del presente estudio son, en su mayoría, comparables con la literatura internacional. 5,7,30,31,33,34 Finalmente, este reporte fue realizado sólo en especialistas en Ortopedia y Traumatología, por lo que no necesariamente refleja la realidad de otras especialidades. Sin embargo, existen reportes internacionales similares entre especialidades quirúrgicas 1,5,8,22,23 y en médicos en formación en Chile.…”
Section: Discussionunclassified
See 1 more Smart Citation